Determinação da solubilidade em sistemas pseudo-ternarios : cravo-da-india (Eugenia caryophyllus) + CO2, gengibre (Zinziber Officinale) + CO2 e erva-doce (Pimpinella anisum) + CO2 - Rodrigues, Vera Maria (2001)
Orientadores: Maria Angela de Almeida Meireles, Marcia Ortiz Mayo Marques